Numerical implementation of the hypoplastic model for SPH analysis of soil structure development in extremely large deformation - Jiao, Hongcheng; Lv, Yaru; Chen, Ding; Huang, Wenxiong; Su, Yuchen (Computers and geotechnics, 2024)
The extremely large deformation of soil is a significant challenge due to the dynamic changes in soil structure, but it is poorly understood owing to inadequate effective numerical methods. This paper presents a numerical method for analysing the responses of sand-like granular soil undergoing extremely large deformation. The proposed method utilizes the Smoothed Particle Hydrodynamics (SPH) technique, which is a meshfree particle-based approach capable of circumventing the computational difficulties associated with mesh distortion. The Gudehus-Bauer (G-B) hypoplastic model, which can capture the pressure- and density- dependent mechanical behaviour of granular soil, is implemented into the in-house developed SPH code. Concerning the characteristics of large deformation, the Green-Naghdi rate is applied in this study to achieve objective stress integration. An adaptive explicit stress integration scheme, termed Modified Euler automatic Substepping with Error Control (M-E-SEC) is utilized to handle the time integration of the SPH equation system. Additionally, a stability correction method is introduced to suppress the breakdown problem that occurs at low-stress states. The effectiveness of the proposed method is validated by experimental data. Furthermore, several numerical examples are presented to elucidate the evolution of shear band structures in granular soils subject to extremely large deformation levels.